2006
DOI: 10.1111/j.2006.0908-8857.03514.x
|View full text |Cite
|
Sign up to set email alerts
|

Breeding territory fidelity in a partial migrant, the American dipper Cinclus mexicanus

Abstract: . 2006. Breeding territory fidelity in a partial migrant, the American dipper Cinclus mexicanus. Á/ J. Avian Biol. 37: 369 Á/ 178.American dipper Cinclus mexicanus populations are frequently composed of resident individuals that occupy permanent territories year round and migratory individuals that overwinter with residents but migrate to breeding territories on higher elevation creeks each spring. Between 1999 and 2004 we examined how migratory strategy (resident/migratory) and sex differences influence breed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Our conclusions are based on the assumption that permanent emigration of residents and migrants is equal and survival estimates are therefore unbiased. We believe this assumption to be true because residents and migrants are highly philopatric to both breeding and wintering territories , Middleton et al 2006). In addition, we monitor eight wintering sites spread over ;40 km, and no individuals of either strategy have permanently moved between sites, suggesting that emigration rates of both migrants and residents are low.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Our conclusions are based on the assumption that permanent emigration of residents and migrants is equal and survival estimates are therefore unbiased. We believe this assumption to be true because residents and migrants are highly philopatric to both breeding and wintering territories , Middleton et al 2006). In addition, we monitor eight wintering sites spread over ;40 km, and no individuals of either strategy have permanently moved between sites, suggesting that emigration rates of both migrants and residents are low.…”
Section: Discussionmentioning
confidence: 98%
“…However, the failure to observe changes in individual behavior does not preclude migration from being a condition-dependent trait. For example, individuals would not be expected to switch strategies if their competitive ability does not change over time or the benefits of breeding site philopatry outweigh the potential gains obtained by switching strategy (Kaitala et al 1993, Middleton et al 2006.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…mexicanus found that annual reproductive success affects pair-bond duration and rate of female return to the same territory in successive years (Middleton et al 2006). Pair-bond duration in turn affects survival (Culina et al 2015) and reproductive success in the following year (Van De Pol et al 2006, S anchez-Macouzet et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…High site fidelity is typical of many territorial species, especially for males defending breeding territories (Greenwood & Harvey 1982). While females may switch territories to increase access to resources or in response to failed breeding attempts (Wauters et al 1995), males are often less likely than females to relocate following reproductive failure (Howlett & Stutchbury 2003;Sedgwick 2004;Middleton et al 2006;Linkhart & Reynolds 2007). Site fidelity, especially between-year fidelity to a specific territory location (i.e.…”
Section: Ethologymentioning
confidence: 99%